The Application of the CRASH-CT Prognostic Model for Older Adults With Traumatic Brain Injury: A Population-Based Observational Cohort Study. Issue 5 (September 2016) - Staples, John A.; Wang, Jin; Mills, Brianna; Temkin, Nancy; Zaros, Mark C.; Jurkovich, Gregory J.; Rivara, Frederick P.
Abstract : Objective: To examine the performance of the Corticosteroid Randomization After Significant Head injury (CRASH) trial prognostic model in older patients with traumatic brain injury. Setting: The National Study on Costs and Outcomes of Trauma cohort, established at 69 hospitals in the United States in 2001 and 2002. Participants: Adults with traumatic brain injury and an initial Glasgow Coma Scale score of 14 or less. Design: The CRASH-CT model predicting death within 14 days was deployed in all patients. Model performance in older patients (aged 65-84 years) was compared with that in younger patients (aged 18-64 years). Main Measures: Model discrimination (as defined by the c-statistic) and calibration (as defined by the Hosmer-Lemeshow P value). Results: CRASH-CT model discrimination was not significantly different between the older ( n = 356; weighted n = 524) and younger patients ( n = 981; weighted n = 2602) and was generally adequate (c-statistic 0.83 vs 0.87, respectively; P = .11). CRASH-CT model calibration was adequate for the older patients and inadequate for younger patients (Hosmer-Lemeshow P values .12 and .001, respectively), possibly reflecting differences in sample size. Calibration-in-the-large showed no systematic under- or overprediction in either stratum. Conclusion: The CRASH-CT model may be valid for use in a geriatric population. Abstract : Supplemental Digital Content is Available in the Text.